Traditional literature review: investigation of rhodamine b on street foods and sauce products in Indonesia - Agsari, Aulia Dwi; Guntarti, Any (Universitas Ahmad Dahlan, 2023)
Food is one of the most important basic human needs for growth and development. Generally, the types of food cater to tastes and look attractive. To make it look attractive and have good taste is usually added with food additives. The food products with the most coloring added are street foods, red sauces, and rainbow cakes that children love. Rhodamine B is a prohibited coloring agent and is not present in food because, for a long time, it will cause liver damage, tumors, and cancer. Therefore, an article review was conducted to determine the levels and methods that can be used to analyze Rhodamine B from several research journals that have been conducted. The literature review method uses the following keywords or terms and strategies: